KONSEP KEADILAN DALAM PRAKTIK POLIGAMI RASULULLAH - Firda Amalia Thoyibah; Nor Fadhila Herniyanti; Rabbiatul Alawiyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This article deals with Polygamy in the Islamic Law Prespective. Polygamy is a man who has more than one to four wives. In the view of Islam, polygamy can be done if it complies with what is clear in the Qur'an, namely, being able to act fair, fair. Then the number of wives may be maximum of four, does not neglect worship of Allah, can keep the honour of his wives, and there is no brotherhood between the former wife and the future wife to be married. Prophet's polygamy is different from what we see today. The practise of the Prophet's polygamy here is not based on biological necessities, but there are some considerations among them wanting to honor a widow, raise the rank of the widows and women who offer themselves for marriage. Nowadays polygamy is based only on biological necessities, and forgetting the element of justice in it. The writing of this article uses library studies/literature studies and qualitative descriptive methods.